Teacher Consultation Efforts of Islamic Religius Education in Improving teacher Professionalism - Komarudin Komarudin; Fikri Rizkia Muhammad; Etep Rohana (Edumaspul: Jurnal Pendidikan, 2022)
The importance of the role of MGMP as a forum for teacher competency development in increasing knowledge, abilities and skills. This study aims to describe in depth the efforts of the PAI MGMP in West Bandung Regency in increasing the professionalism of PAI teachers at West Bandung Junior High School and provide an explanation of the effectiveness of the PAI Cluster 4 MGMP in West Bandung Regency in increasing the professionalism of PAI teachers in SMP and to find out the problems of the PAI Cluster 4 MGMP in Bandung Regency. West in increasing the professionalism of PAI teachers in West Bandung Regency Junior High School. This research is qualitative research by taking the background of MGMP PAI Cluster 4, West Bandung Regency. Data was collected by conducting observations, in-depth interviews and documentation. Data analysis was carried out by giving meaning to the data that had been collected and from that meaning drawn conclusions. Checking the validity of the data is done by using triangulation, by means of Check recheck and Cross checking. The results showed: (1) MGMP PAI efforts in West Bandung Regency in improving the professionalism of teachers, are through supervision, coaching, and training which are manifested in routine programs and development programs, through which teacher competence is expected to increase (2) MGMP has not been running effectively because Management is not optimal and MGMP standards are not met (3) Barriers faced by MGMP PAI Cluster 4 West Bandung Regency, namely the large area and complexity of teacher problems, MGMP cannot reflect the real needs of each school or teacher, MGMP management has not run properly good, and inadequate funding for MGMP operations. (4) the solution to the problem carried out by MGMP PAI Cluster 4 is to create a stronger network between members, utilize telecommunications and internet media, optimize deliberation and consensus in every meeting.